Nomenclatural revision of Ficus sect. Americanae (Moraceae): typification of Ficus americana and allied species - Pederneiras, Leandro Cardoso; Romaniuc-Neto, Sergio; Mansano, Vidal De Freitas (Phytotaxa, 2018)
Ficus sect. Americanae has ca. 160 accepted species and approximately 650 binomials in the neotropical region, many of which do not have a clearly designated holotype, lectotype, or neotype. In the present study, we revised all names of F. americana and allied species. With this, we designated a neotype for F. rojasi and lectotypes for the 22 following names: Ficus americana subsp. subapiculata, F. anacardiifolia, F. aureo-brunnea, F. bunquensis, F. chiribiquetensis, F. chiriquiana, F. coerulescens, F. corpulenta, F. cundinamarcensis, F. fresnoensis, F. eugeniifolia, F. jacquiniifolia, F. liebmanniana, F. maitin, F. maroana, F. martinii, F. microclada, F. oblanceolata, F. oerstediana, F. prinoides, F. splendens, and F. umbonigera.